A bimetallic element doped silicon dioxide composite nanomaterial and its preparation method and application

Through the preparation method of bimetallic element-doped silica composite nanomaterials, the hollow mesoporous structure is constructed in one step by using complexation reaction and solubilized thermal reaction, which solves the problem of complex process and difficult to control the morphology of the template method, and achieves efficient preparation and application Nanomaterials in the catalysis and energy fields.

CN115957762BInactive Publication Date: 2025-01-17DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202111178826.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-10-11
Publication Date
2025-01-17
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

When constructing hollow nanostructures in the prior art, the template method has complex process and difficult to control the morphology, and is not suitable for large-scale preparation of multifunctional composite nanomaterials.

Method used

Using a preparation method of bimetallic element-doped silica composite nanomaterials, template removal and hollow mesoporous structure construction are achieved through complexation reaction and solvothermal reaction in one step, using metal coordination polymers as hard templates and metal sources. Achieve uniform distribution of bimetallic elements and the formation of mesoporous structures.

Benefits of technology

The preparation of hollow mesoporous silica composite nanomaterials with high specific surface area, adjustable cavity size and metal distribution is achieved. It is suitable for catalysis, energy utilization and conversion fields, with simple preparation technology and high yield.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0003296496770000011
    Figure HDA0003296496770000011
  • Figure HDA0003296496770000012
    Figure HDA0003296496770000012
  • Figure HDA0003296496770000021
    Figure HDA0003296496770000021
Patent Text Reader

Abstract

The present application discloses a bimetallic element doped silicon dioxide composite nanomaterial and its preparation method and application. The composite nanomaterial comprises a metal element and silicon dioxide with a hollow shell structure; the metal element is selected from at least two of zinc, cobalt, nickel, manganese, copper or iron; the internal cavity size is 50 to 500 nm; the specific surface area is 500 to 1000 m 2 / g, pore volume is 1.2~2.0cm 3 / g. The process of this application is simple, and the removal of the template and the construction of a complex hollow mesoporous structure are achieved at the same time. The rich and ordered metal composition and unique coordination instability of the coordination polymer are used as a metal source and a structure-guided template to form an internal cavity and dope metal elements at the same time. The material has a regular morphology, uniform size, good dispersion, single / double shell and hollow structure, high specific surface area and large pore volume, and has good application prospects in catalysis, energy utilization and conversion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of material preparation, and specifically relates to a bimetallic element doped silica composite nanomaterial and a preparation method and application thereof. Background Art

[0002] Micro / nanoscale design and regulation of material structure have attracted widespread attention. By comparing materials with different morphologies, pores and multi-level structures, the improvement of reaction performance by structure is revealed. Hollow mesoporous nanomaterials are endowed with special physical and chemical properties and application value due to the presence of cavities and pores. In addition, since the synergistic and coupling effects between multiple components (metal-metal, metal-support) have been shown to significantly improve the activity and stability of catalytic reactions, it is very necessary to develop complex hollow nanocomposites in order to further meet the special needs of catalysis and energy utilization. However, the directional introduction and precise position control of different metal components in the material is a key challenge.

[0003] Template methods are widely used in the construction of hollow nanostructures. Most of these processes use hard spheres such as silica or polystyrene as hard templates, which often require etchants or high-temperature calcination to remove the templates. The process is complex and the morphology is difficult to control. In addition, such templates need to be specifically functionalized or coated to obtain multifunctional composite nanomaterials, which involves multiple material synthesis and separation steps and is not suitable for mass production of materials. Summary of the invention

[0004] The present application relates to a method for preparing a hollow mesoporous silica composite nanomaterial doped with bimetallic elements. The method is simple, has a high yield, and has good stability. Two different metal elements can be introduced in situ at the same time. The nanocomposite material prepared by this method has adjustable cavity size, shell structure, metal content and metal distribution, and has good application prospects in the fields of catalysis, energy utilization and conversion.

[0005] According to one aspect of the present application, there is provided a metal element doped silicon dioxide composite nanomaterial, comprising a metal element and silicon dioxide;

[0006] The metal element is doped into silicon dioxide;

[0007] The metal element is selected from at least two of zinc, cobalt, nickel, manganese, copper or iron; the content of the metal element is 0.5% to 20wt% of the metal element-doped silicon dioxide composite nanomaterial;

[0008] The microstructure of the composite nano material is a hollow spherical shell.

[0009] The inner diameter of the hollow spherical shell is 50 to 500 nm;

[0010] The specific surface area of ​​the composite nanomaterial is 500 to 1000 m 2 / g;

[0011] The spherical shell has mesopores; the pore diameter of the mesopores is 2 to 20 nm; the pore volume of the mesopores is 1.2 to 2.0 cm 3 / g.

[0012] The hollow spherical shell is a single shell or a double shell, and the metal elements are evenly distributed in the shell.

[0013] According to another aspect of the present application, a method for preparing the above-mentioned metal element-doped silicon dioxide composite nanomaterial is provided, comprising the following steps:

[0014] (1) mixing a raw material containing a metal element precursor and an organic ligand with a solvent, causing a complex reaction, and drying I to obtain a metal coordination polymer;

[0015] (2) mixing the raw material containing the silane precursor and the metal coordination polymer obtained in (1) with a surfactant, aqueous ammonia, and ethanol to obtain a mixed solution, subjecting the mixed solution to a solvent thermal reaction, drying II, and calcining to obtain the metal element-doped silica composite nanomaterial;

[0016] The organic ligand is selected from imidazole organic ligands or organic acid organic ligands.

[0017] Further, the following steps are included:

[0018] (1) mixing a raw material containing a metal element precursor and an organic ligand with a solvent, stirring I, performing a complex reaction, centrifuging I, and drying I to obtain a metal coordination polymer;

[0019] (2) Mixing the raw material containing the silane precursor and the metal coordination polymer obtained in (1) with a surfactant, ammonia water, and ethanol, stirring II, causing a solvent thermal reaction, centrifuging II, and drying II to obtain the bimetallic element-doped silica composite nanomaterial.

[0020] (1) In:

[0021] The metal element precursor is selected from at least one of nitrates, acetates and sulfates of the metal element;

[0022] The imidazole organic ligand is 2-methylimidazole;

[0023] The organic acid organic ligand is selected from at least one of trimesic acid and terephthalic acid;

[0024] The molar ratio of the organic ligand to the metal element precursor is 1 to 16, calculated based on the molar ratio of the metal element in the metal element precursor;

[0025] The solvent is selected from at least one of N,N-dimethylformamide, methanol, ethanol and water;

[0026] The reaction temperature is 20-150° C., and the reaction time is 6-24 hours.

[0027] The reaction is carried out under continuous stirring conditions; the stirring speed is 300-700 rpm;

[0028] The metal coordination polymer is subjected to centrifugation I and drying I; the rotation speed of the centrifugation I is 6000-10000 rpm;

[0029] The metal coordination polymer is dried I; the temperature of the drying I is 60-100°C.

[0030] (2) In:

[0031] In the mixed solution, the surfactant is selected from at least one of hexadecyltrimethylammonium bromide, dodecyltrimethylammonium chloride, octadecyltrimethylammonium bromide and hexadecyltrimethylammonium chloride; the concentration of the surfactant in the mixed solution is 0.003-0.03 g / mL;

[0032] The concentration of the ammonia water is 25-28%; the volume ratio of the ammonia water to the mixed solution is 6-40 μL / mL;

[0033] The ethanol is an ethanol aqueous solution, wherein the volume ratio of ethanol to water in the ethanol aqueous solution is 0.4 to 10;

[0034] The silane precursor is tetraethyl orthosilicate; the concentration of tetraethyl orthosilicate in the mixed solution is 5 to 50 μL / mL;

[0035] Optionally, the silane precursor further contains an auxiliary silane; the auxiliary silane is selected from at least one of propyl orthosilicate, 3-aminopropyltriethoxysilane, 1,2-bis(triethoxysilyl)ethane, mercaptopropyltrimethoxysilane, and bis-[3-(triethoxysilyl)propyl]tetrasulfide; the concentration of the auxiliary silane in the mixed solution is less than 50 μL / mL;

[0036] The temperature of the solvent thermal reaction is 60 to 160° C.; the time of the solvent thermal reaction is 3 to 36 hours.

[0037] The calcination atmosphere is selected from nitrogen, argon, helium, air, and mixed oxygen-containing gases; the calcination temperature is 300-900° C.; and the calcination time is 2-8 hours.

[0038] The solvothermal reaction is first carried out under stirring conditions; the stirring speed II is 300-700 rpm; then the solvothermal reaction is carried out; the solvothermal reaction is carried out under static conditions;

[0039] The metal element doped silicon dioxide composite nanomaterial is subjected to centrifugation II and drying II; the rotation speed of the centrifugation II is 6000-10000 rpm;

[0040] The metal element doped silicon dioxide composite nano material is dried II; the temperature of the drying II is 60-100°C.

[0041] According to another aspect of the present application, there is provided an application of the above-mentioned metal element doped silica composite nanomaterial or the bimetallic element doped silica composite nanomaterial prepared by the above-mentioned preparation method, in which, in the carbon dioxide hydrogenation reaction, a carbon dioxide conversion rate of 10 to 60% is achieved, and the product is carbon monoxide, also including methane and methanol, wherein the selectivity of the main product carbon monoxide is 60 to 95%.

[0042] Compared with the prior art, this application has the following advantages and effects:

[0043] 1. The preparation technology is simple, and the one-step solvothermal process can simultaneously achieve the removal of the template and the construction of the hollow mesoporous complex structure. In addition, metal coordination polymers play a dual role due to their rich and ordered metal composition and unique coordination instability. They not only serve as hard templates to form internal cavities, but also provide bimetallic element doping for the final product. They can serve as metal sources and structure-guided templates at the same time, which provides a good basic material for the synthesis of hollow composite nanomaterials.

[0044] 2. The silica composite material has regular morphology, uniform size, good dispersion, single / double shell and hollow structure, high specific surface area and large pore volume.

[0045] 3. By precisely controlling the type and proportion of metal salts, the amount of silicon oxide precursor, solvent thermal time and temperature, the bimetallic element content, metal position, shell structure, shell thickness and cavity size in the final product can be easily changed. The method is simple, with high yield and good stability. It has good application prospects in the fields of catalysis, energy utilization and conversion, and can meet the needs of different applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] Figure 1 This is a transmission electron micrograph of the Zn, Co doped-hollow mesoporous silica composite nanomaterial prepared under the conditions of Example 1 of the present application.

[0047] FIG. 2 is a nitrogen adsorption curve (a) and a pore size distribution diagram (b) of the Zn, Co doped-hollow mesoporous silica composite nanomaterial prepared under the conditions of Example 1 of the present application.

[0048] Figure 3 This is a transmission electron microscope image of the Zn, Ni doped-hollow mesoporous silica composite nanomaterial prepared under the conditions of Example 2 of the present application.

[0049] Figure 4 This is the X-ray diffraction pattern of the Ni, Co doped-hollow mesoporous silica composite nanomaterial prepared under the conditions of Example 3 of the present application.

[0050] FIG5 shows the activity (a) and selectivity (b) of the Zn, Co doped-hollow mesoporous silica composite nanomaterial prepared under the conditions of Example 1 of the present application in the carbon dioxide hydrogenation reaction.

[0051] Figure 6 This is a transmission electron micrograph of a Zn, Co doped hollow mesoporous silica composite nanomaterial prepared under the conditions of Example 4 of the present application. DETAILED DESCRIPTION

[0052] The present application is described in detail below with reference to embodiments, but the present application is not limited to these embodiments.

[0053] Unless otherwise specified, the raw materials in the examples of the present application were purchased through commercial channels, among which zinc nitrate hexahydrate, cobalt nitrate hexahydrate, nickel nitrate hexahydrate, methanol, N,N-dimethylformamide, ethanol, ammonia water, hexadecyltrimethylammonium bromide, hexadecyltrimethylammonium chloride, octadecyltrimethylammonium bromide, and tetraethyl orthosilicate were purchased from Sinopharm Chemical Reagent Co., Ltd.; 2-methylimidazole and trimesic acid were purchased from Aladdin Reagent Co., Ltd.; 3-aminopropyltriethoxysilane and mercaptopropyltrimethoxysilane were purchased from Sigma-Aldrich Reagent Co., Ltd.

[0054] The analysis method in the examples of this application is as follows:

[0055] Transmission electron microscope analysis was performed using Hitachi 7700 from Hitachi, Japan; nitrogen adsorption test was performed using ASAP2460 multifunctional adsorption instrument from Micromeritics, USA; and X-ray diffraction analysis was performed using D / Max 2500 / PC from Rigaku Corporation, Japan.

[0056] Example 1

[0057] 0.84 g Zn(NO3)2·6H2O and 0.822 g Co(NO3)2·6H2O were dissolved in 120 mL methanol to form a solution. 40 mL methanol containing 3.70 g 2-methylimidazole was poured into the above solution. Stir at room temperature for 20 hours, collect the precipitate by centrifugation, wash it 3 times with methanol, and finally dry it at 60°C overnight to obtain Zn, Co-metal coordination polymer. 0.1 g hexadecyltrimethylammonium bromide was dissolved in a mixture of water (20 mL), ethanol (8 mL), and ammonia water (0.2 mL, 25 wt%), stirred at room temperature for 30 min, and then 0.1 g Zn, Co-metal coordination polymer was added. After ultrasonic dispersion, 450 μL of tetraethyl orthosilicate solution was added to the suspension. The mixture was stirred at room temperature for 24 hours, and then placed in a polytetrafluoroethylene-lined autoclave and heated at 100°C for 3 hours. The solid product was recovered by centrifugation and dried at 60°C, and then placed in a tube furnace and calcined at 500°C for 4 hours under a nitrogen atmosphere to obtain a Zn, Co doped-hollow mesoporous silica composite nanomaterial with a double shell.

[0058] Figure 1 This is a transmission electron microscope image of the Zn, Co doped-hollow mesoporous silica composite nanomaterial prepared under the conditions of Example 1 of this application. Figure 1 It can be seen that the nanomaterial has a double-shell hollow structure, the internal cavity size is about 90nm, and the distance between the two shells is about 35nm.

[0059] Figure 2 shows the nitrogen adsorption curve (a) and pore size distribution diagram (b) of the Zn, Co doped-hollow mesoporous silica composite nanomaterial prepared under the conditions of Example 1 of the present application. It can be seen from Figure 2 that the nanomaterial has a typical IV-shaped isotherm, indicating that it contains a mesoporous structure and has a specific surface area of ​​925 m 2 / g, pore diameters of 2.4nm and 14.8nm, and pore volume of 1.77cm 3 / g.

[0060] Figure 5 shows the activity (a) and selectivity (b) of the Zn, Co doped-hollow mesoporous silica composite nanomaterial prepared under the conditions of Example 1 of the present application in the carbon dioxide hydrogenation reaction. It can be seen from Figure 5 that when the reaction temperature is 390°C, the carbon dioxide conversion rate of the material is 12%, and the activity gradually increases with the increase of temperature. The reaction product is mainly carbon monoxide (60%), and the selectivity remains stable in the temperature range of 390-470°C.

[0061] Example 2

[0062] 0.446g Zn(NO3)2·6H2O and 0.436g Ni(NO3)2·6H2O were dissolved in 30mL methanol to form a solution. 20mL methanol containing 1.97g 2-methylimidazole was poured into the above solution. Stir at room temperature for 24 hours, collect the precipitate by centrifugation, wash it 3 times with methanol, and finally dry it at 60°C overnight to obtain Zn, Ni-metal coordination polymer. 0.1g hexadecyltrimethylammonium bromide was dissolved in a mixture of water (20mL), ethanol (8mL), and ammonia water (0.2mL, 25wt%), stirred at room temperature for 30min, and then 0.1g Zn, Ni-metal coordination polymer was added. After ultrasonic dispersion, 300μL of tetraethyl orthosilicate solution was added to the suspension. The mixture was stirred at room temperature for 24 hours, and then placed in a polytetrafluoroethylene-lined autoclave and heated at 100°C for 24 hours. The solid product was recovered by centrifugation and dried at 60°C, and then placed in a tube furnace and calcined at 700°C for 4 hours under a nitrogen atmosphere to obtain a Zn, Ni doped-hollow mesoporous silica composite nanomaterial with a single shell.

[0063] Figure 3 This is a transmission electron microscope image of the Zn, Ni doped-hollow mesoporous silica composite nanomaterial prepared under the conditions of Example 2 of this application. Figure 3 It can be seen that the material is a hollow mesoporous nanoparticle with a single shell, and the internal cavity size is about 150nm.

[0064] Example 3

[0065] Dissolve 0.36g Ni(NO3)2·6H2O and 0.36g Co(NO3)2·6H2O in 30mL N,N-dimethylformamide to form a solution. Pour 30mL N,N-dimethylformamide containing 0.15g trimesic acid into the above solution. Stir at 150℃ for 6 hours, collect the precipitate by centrifugation, wash it 3 times with N,N-dimethylformamide, and finally dry it at 60℃ overnight to obtain Ni,Co-metal coordination polymer. Dissolve 0.1g hexadecyltrimethylammonium bromide in a mixture of water (20mL), ethanol (8mL), and ammonia water (0.2mL, 25wt%), stir at room temperature for 30min, and then add 0.1g Ni,Co-metal coordination polymer. After ultrasonic dispersion, add 300μL of tetraethyl orthosilicate solution to the suspension. The mixture was stirred at room temperature for 24 hours and then placed in a polytetrafluoroethylene-lined autoclave and heated at 100°C for 3 hours. The solid product was recovered by centrifugation and dried at 60°C, and then placed in a tubular furnace and calcined at 700°C for 4 hours under a nitrogen atmosphere to obtain a Ni, Co doped-hollow mesoporous silica composite nanomaterial with a single shell.

[0066] Figure 4 This is the X-ray diffraction pattern of the Ni, Co doped-hollow mesoporous silica composite nanomaterial prepared under the conditions of Example 3 of the present application. This figure proves the existence of the metal NiCo alloy (2θ=44.5°, 51.8°, 76.4°) and amorphous silicon oxide (2θ=23°).

[0067] Example 4

[0068] 0.42g Zn(NO3)2·6H2O and 0.411g Co(NO3)2·6H2O were dissolved in 120mL methanol to form a solution. 40mL methanol containing 1.85g 2-methylimidazole was poured into the above solution. Stir at 20°C for 6 hours, collect the precipitate by centrifugation, wash it 3 times with methanol, and finally dry it at 60°C overnight to obtain Zn, Co-metal coordination polymer. 0.2g hexadecyltrimethylammonium bromide was dissolved in a mixture of water (20mL), ethanol (8mL), and ammonia water (0.2mL, 25wt%), stirred at room temperature for 30min, and then 0.1g Zn, Co-metal coordination polymer was added. After ultrasonic dispersion, 600μL of tetraethyl orthosilicate solution was added to the suspension. The mixture was stirred at room temperature for 3 hours, and then placed in a polytetrafluoroethylene-lined autoclave and heated at 100°C for 24 hours. The solid product was recovered by centrifugation and dried at 60°C, and then placed in a muffle furnace and calcined at 500°C for 4 hours in an air atmosphere to obtain a Zn, Co doped-hollow mesoporous silica composite nanomaterial with a double shell.

[0069] Figure 6 This is a transmission electron microscope image of a Zn, Co doped-hollow mesoporous silica composite nanomaterial prepared under the conditions of Example 4 of the present application. From the image, it can be seen that the nanomaterial has good dispersion, uniform size of about 230nm, and a double-shell hollow structure, the size of its internal cavity is about 160nm, and the distance between the two shells is about 40nm.

[0070] Example 5

[0071] 3.360g Zn(NO3)2·6H2O and 0.328g Co(NO3)2·6H2O were dissolved in 120mL methanol to form a solution. 40mL methanol containing 3.70g 2-methylimidazole was poured into the above solution. Stir at room temperature for 24 hours, collect the precipitate by centrifugation, wash it 3 times with methanol, and finally dry it at 60°C overnight to obtain Zn, Co-metal coordination polymer. 0.1g hexadecyltrimethylammonium bromide was dissolved in a mixture of water (20mL), ethanol (8mL), and ammonia water (0.2mL, 25wt%), stirred at room temperature for 30min, and then 0.1g Zn, Co-metal coordination polymer was added. After ultrasonic dispersion, 150μL of tetraethyl orthosilicate solution was added to the suspension. The mixture was stirred at room temperature for 10 hours, and then placed in a polytetrafluoroethylene-lined autoclave and heated at 100°C for 12 hours. The solid product was recovered by centrifugation and dried at 60°C, and then placed in a muffle furnace and calcined at 300°C for 2 hours in an air atmosphere to obtain a Zn, Co doped-hollow mesoporous silica composite nanomaterial with a single shell.

[0072] Example 6

[0073] 0.84 g of Co(NO3)2·6H2O and 0.411 g of Ni(NO3)2·6H2O were dissolved in 120 mL of methanol to form a solution. 40 mL of methanol containing 3.70 g of 2-methylimidazole was poured into the above solution. Stir at room temperature for 8 hours, collect the precipitate by centrifugation, wash it 3 times with methanol, and finally dry it at 60°C overnight to obtain Co, Ni-metal coordination polymer. 0.2 g of hexadecyltrimethylammonium bromide was dissolved in a mixture of water (20 mL), ethanol (10 mL), and ammonia water (0.8 mL, 25 wt%), stirred at room temperature for 30 min, and then 0.1 g of Co, Ni-metal coordination polymer was added. After ultrasonic dispersion, 350 μL of tetraethyl orthosilicate solution was added to the suspension. The mixture was stirred at room temperature for 12 hours, and then placed in a polytetrafluoroethylene-lined autoclave and heated at 100°C for 36 hours. The solid product was recovered by centrifugation and dried at 60°C, and then placed in a muffle furnace and calcined at 500°C for 8 hours in an air atmosphere to obtain a Co, Ni doped-hollow mesoporous silica composite nanomaterial with a double shell.

[0074] Example 7

[0075] 0.42g Zn(NO3)2·6H2O and 0.411g Co(NO3)2·6H2O were dissolved in 120mL water to form a solution. 40mL water containing 0.23g 2-methylimidazole was poured into the above solution. Stir at room temperature for 20 hours, collect the precipitate by centrifugation, wash with water 3 times, and finally dry at 60°C overnight to obtain Zn, Co-metal coordination polymer. 0.1g hexadecyltrimethylammonium bromide was dissolved in a mixture of water (20mL), ethanol (10mL), and ammonia water (0.8mL, 25wt%), stirred at room temperature for 30min, and then 0.1g Zn, Co-metal coordination polymer was added. After ultrasonic dispersion, 250μL of tetraethyl orthosilicate solution was added to the suspension. The mixture was stirred at room temperature for 6 hours, and then placed in a polytetrafluoroethylene-lined autoclave and heated at 160°C for 3 hours. The solid product was recovered by centrifugation and dried at 60°C, and then placed in a tube furnace and calcined at 900°C for 2 hours under an argon atmosphere to obtain a Zn, Co doped-hollow mesoporous silica composite nanomaterial with a single shell.

[0076] Example 8

[0077] Dissolve 0.336g Zn(NO3)2·6H2O and 3.288g Ni(NO3)2·6H2O in 120mL ethanol to form a solution. Pour 40mL ethanol containing 3.70g 2-methylimidazole into the above solution. Stir at room temperature for 15 hours, collect the precipitate by centrifugation, wash it with ethanol 3 times, and finally dry it at 60°C overnight to obtain Zn, Ni-metal coordination polymer. Dissolve 0.1g octadecyltrimethylammonium bromide in a mixture of water (20mL), ethanol (8mL), and ammonia water (0.2mL, 25wt%), stir at room temperature for 30min, and then add 0.1g Zn, Ni-metal coordination polymer. After ultrasonic dispersion, add 150μL of ethyl orthosilicate solution and 1400μL of 3-aminopropyltriethoxysilane solution to the suspension. The mixture was stirred at room temperature for 18 hours and then placed in a polytetrafluoroethylene-lined autoclave and heated at 60°C for 36 hours. The solid product was recovered by centrifugation and dried at 60°C, and then placed in a tube furnace and calcined at 500°C for 6 hours under a helium atmosphere to obtain a Zn, Ni doped-hollow mesoporous silica composite nanomaterial with a single shell.

[0078] Example 9

[0079] 0.329g Zn(NO3)2·6H2O and 1.344g Ni(NO3)2·6H2O were dissolved in 100mL methanol to form a solution. 100mL methanol containing 7.40g 2-methylimidazole was poured into the above solution. Stir at room temperature for 20 hours, collect the precipitate by centrifugation, wash it 3 times with methanol, and finally dry it at 60°C overnight to obtain Zn, Ni-metal coordination polymer. 0.8g hexadecyltrimethylammonium chloride was dissolved in a mixture of water (20mL), ethanol (8mL), and ammonia water (0.2mL, 25wt%), stirred at room temperature for 30min, and then 0.1g Zn, Ni-metal coordination polymer was added. After ultrasonic dispersion, 1400μL of tetraethyl orthosilicate solution was added to the suspension. The mixture was stirred at room temperature for 3 hours, and then placed in a polytetrafluoroethylene-lined autoclave and heated at 100°C for 15 hours. The solid product was recovered by centrifugation and dried at 60°C, and then placed in a tube furnace and calcined at 500°C for 4 hours in a mixed oxygen atmosphere to obtain a Zn, Ni doped-hollow mesoporous silica composite nanomaterial with a single shell.

[0080] Example 10

[0081] 0.56g Ni(NO3)2·6H2O and 0.822g Co(NO3)2·6H2O were dissolved in 60mL N,N-dimethylformamide to form a solution. 40mL N,N-dimethylformamide containing 3.70g terephthalic acid was poured into the above solution. Stir at 140°C for 12 hours, collect the precipitate by centrifugation, wash it 3 times with N,N-dimethylformamide, and finally dry it at 60°C overnight to obtain Ni,Co-metal coordination polymer. 0.2g hexadecyltrimethylammonium bromide was dissolved in a mixture of water (8mL), ethanol (80mL), and ammonia water (3.5mL, 25wt%), stirred at room temperature for 30min, and then 0.1g Ni,Co-metal coordination polymer was added. After ultrasonic dispersion, 900μL of ethyl orthosilicate solution and 300μL of mercaptopropyltrimethoxysilane were added to the suspension. The mixture was stirred at room temperature for 24 hours and then placed in a polytetrafluoroethylene-lined autoclave and heated at 140°C for 6 hours. The solid product was recovered by centrifugation and dried at 60°C, and then placed in a muffle furnace and calcined at 900°C for 4 hours in an air atmosphere to obtain a Ni, Co doped-hollow mesoporous silica composite nanomaterial with a single shell.

[0082] The above are only a few embodiments of the present application and do not constitute any form of limitation to the present application. Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the present application. Any technician familiar with the profession, without departing from the scope of the technical solution of the present application, using the technical content disclosed above to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A metal element doped silica composite nanomaterial, characterized in that: Includes metallic elements and silicon dioxide; The metal element is doped into silicon dioxide; The metal element is selected from at least two of zinc, cobalt and nickel; the content of the metal element is 0.5% to 20wt% of the metal element-doped silicon dioxide composite nanomaterial; The microstructure of the composite nanomaterial is a hollow spherical shell; The composite nanomaterial is prepared by the following steps: (1) mixing a raw material containing a metal element precursor and an organic ligand with a solvent, causing a complex reaction, and drying I to obtain a metal coordination polymer; (2) mixing the raw material containing the silane precursor and the metal coordination polymer obtained in (1) with a surfactant, aqueous ammonia, and ethanol to obtain a mixed solution, subjecting the mixed solution to a solvent thermal reaction, drying II, and calcining to obtain the metal element-doped silica composite nanomaterial; The organic ligand is selected from imidazole organic ligands or organic acid organic ligands; The metal element precursor is selected from at least one of nitrates, acetates and sulfates of the metal element; The imidazole organic ligand is 2-methylimidazole; The organic acid organic ligand is selected from at least one of trimesic acid and terephthalic acid; The surfactant is selected from at least one of hexadecyltrimethylammonium bromide, dodecyltrimethylammonium chloride, octadecyltrimethylammonium bromide and hexadecyltrimethylammonium chloride; The silane precursor is tetraethyl orthosilicate.

2. The composite nanomaterial according to claim 1, characterized in that: The inner diameter of the hollow spherical shell is 50 to 500 nm; The specific surface area of ​​the composite nanomaterial is 500 to 1000 m 2 / g; The spherical shell has mesopores; the pore diameter of the mesopores is 2 to 20 nm; the pore volume of the mesopores is 1.2 to 2.0 cm 3 / g.

3. The composite nanomaterial according to claim 1, characterized in that: The hollow spherical shell is a single shell or a double shell.

4. The composite nanomaterial according to claim 1, characterized in that: (1) In: The molar ratio of the organic ligand to the metal element precursor is 1 to 16, calculated based on the molar ratio of the metal element in the metal element precursor; The solvent is selected from at least one of N,N-dimethylformamide, methanol, ethanol and water; The reaction temperature is 20-150° C., and the reaction time is 6-24 hours.

5. The composite nanomaterial according to claim 1, characterized in that: (1): The reaction is carried out under continuous stirring conditions; The metal coordination polymer is dried I; the temperature of the drying I is 60-100°C.

6. The composite nanomaterial according to claim 1, characterized in that: In the mixed solution described in (2): The concentration of the surfactant in the mixed solution is 0.003 to 0.03 g / mL; The concentration of the ammonia water is 25-28%; the volume ratio of the ammonia water to the mixed solution is 6-40 μL / mL; The ethanol is an ethanol aqueous solution, wherein the volume ratio of ethanol to water in the ethanol aqueous solution is 0.4 to 10; The concentration of the tetraethyl orthosilicate in the mixed solution is 5 to 50 μL / mL; The silane precursor further contains an auxiliary silane; the auxiliary silane is selected from at least one of propyl orthosilicate, 3-aminopropyltriethoxysilane, 1,2-bis(triethoxysilyl)ethane, mercaptopropyltrimethoxysilane, and bis-[3-(triethoxysilyl)propyl]tetrasulfide; the concentration of the auxiliary silane in the mixed solution is less than 50 μL / mL; The temperature of the solvent thermal reaction is 60 to 160° C.; the time of the solvent thermal reaction is 3 to 36 hours.

7. The composite nanomaterial according to claim 1, characterized in that: The calcination atmosphere in (2) is selected from nitrogen, argon, helium, air, and mixed oxygen-containing gases; the calcination temperature is 300 to 900° C.; and the calcination time is 2 to 8 hours.

8. The composite nanomaterial according to claim 1, characterized in that: The metal element doped silica composite nanomaterial in (2) is dried II; the drying temperature of II is 60-100°C.

9. An application of the metal element doped silicon dioxide composite nanomaterial according to any one of claims 1 to 8, characterized in that: In the carbon dioxide hydrogenation reaction, the carbon dioxide conversion rate is 10-60%, and the product is carbon monoxide, methane and methanol, wherein the selectivity of the main product carbon monoxide is 60-95%.

Citation Information

Cited By

  • SiO2-metal oxide composite material with high specific surface area as well as preparation method and application thereof

    CN119701969A